Omejitve obresti - včeraj, danes, jutri - Zgaga, Matevž (Pravni letopis, 2025)
Abstract The legal institution of interest rate restrictions is as old as the law itself. This article focuses on development over the last 150 years, the current stage of which is represented by the new Directive (EU) 2023/2225 on credit agreements for consumers. The Directive has introduced a loose obligation on Member States to adopt measures to effectively prevent abuse, such as interest rate caps. Although Slovenia is among the many Member States that already had such caps in place before the adoption of the Directive, some additional restrictions are expected in the near future.
Keywords: bančno poslovanje; consumer credit; consumer protection; Directive 2023/2225; Direktiva 2023/2225; interest; obresti; potrošniški kredit; retail banking; varstvo potrošnikov; ZPotK-3